(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article analyzes scientific approaches to the problem of abuse of rights and examines it in the narrow context of the application of legal instruments in the professional activity of an advocate. The focus is on examining whether the provisions prohibiting an advocate from abusing rights have the characteristics of a legal norm. It is noted that abuse, which contains an element of the ethically- derived concept of “evil,” cannot be precisely defined legally. At the same time, rights that may be subject to abuse may derive from both direct provisions and the peculiarities of the general permissive principle. Since offenses and violations of legal norms are not identical categories, the issue of using a state of irresponsibility is considered separately from the abuse of rights. Using the dogmatic method, it is established that, under the Criminal Code of Ukraine, abuse as a form of improper exercise of rights is a characteristic of intentional conduct; however, this characteristic is not necessarily associated with a selfish motive or an intent to harm another person. It has been proven that the subject of criminalized abuse may be either (subjective) rights or other phenomena related to such rights, such as official position, authority, etc. It is concluded that the prohibition on abusing rights lacks sufficient characteristics of a legal norm. Moreover, the provisions on the inadmissibility of abuse of rights by a defense attorney or advocate lack sufficient legal certainty. In particular, abuse of procedural rights by a defense attorney in criminal proceedings, which may consist only of delaying the proceedings, although it may be terminated by the court, does not entail liability as such, and the decision on the existence of signs of such abuse is purely discretionary.